Variation in ectomycorrhizal fungal communities associated with Silver linden (Tilia tomentosa) within and across urban areas. Issue 12 (12th October 2018) - Van Geel, Maarten; Yu, Kang; Ceulemans, Tobias; Peeters, Gerrit; van Acker, Kasper; Geerts, Willem; Ramos, Miguel A; Serafim, Cindy; Kastendeuch, Pierre; Najjar, Georges; Ameglio, Thierry; Ngao, Jérôme; et al.
ABSTRACT: Trees in urban areas face harsh environmental conditions. Ectomycorrhizal fungi (EcM) form a symbiosis with many tree species and provide a range of benefits to their host through their extraradical hyphal network. Although our understanding of the environmental drivers and large scale geographical variation of EcM communities in natural ecosystems is growing, our knowledge of EcM communities within and across urban areas is still limited. Here, we characterized EcM communities using Illumina miseq sequencing on 175 root samples of the urban tree Tilia tomentosa from three European cities, namely Leuven (Belgium), Strasbourg (France) and Porto (Portugal). We found strong differences in EcM richness and community composition between cities. Soil acidity, organic matter and moisture content were significantly associated with EcM community composition. In agreement, the explained variability in EcM communities was mostly attributed to general soil characteristics, whereas very little variation was explained by city and heavy metal pollution. Overall, our results suggest that EcM communities in urban areas are significantly associated with soil characteristics, while heavy metal pollution and biogeography had little or no impact. These findings deliver new insights into EcM distribution patterns in urban areas and contribute to specific inoculation strategies to improve urban tree vitality. Abstract : Ectomycorrhizal communities in urban areas are significantly related to soil characteristics, while heavy metal pollution and biogeography had little or no effect.